Wave-generated Forecast in Weda Bay, Central Halmahera, Based on Wind and Satellite Data - Jesikha Dwi Aprilia; Mohammad Ridwan Lessy; Nani Nagu (Department of Marine Sciences, Trunojoyo University of Madura, Indonesia, 2025)
ABSTRACTOcean waves are an important oceanographic parameter to analyse due to their role in ocean circulation, marine transportation, and coastal management. This research focused on forecasting the height and duration of significant waves in the Weda Bay, utilizing wind data from meteorological stations and altimetry satellite data. The data utilized comprised maximum wind speed and direction records spanning ten years, from 2011 to 2021, collected from two meteorological stations: Baabullah Station in Ternate and Gamar Malamo in Galela. Simultaneously, AVISIO Altimetry satellite data is retrieved from a website that aligns with the temporal measurement range of meteorological station data. The analysis phase initiates with wind speed correction, effective fetch calculation, and high and periodic wave forecasting utilizing Excel software, while satellite data is examined using ArcGIS software. The prediction results for wave height and period indicate that data from the Baabullah station show a significant wave height ranging from 0.00 to 2.33 meters and a significant wave period from 0.09 to 5.07 seconds. In contrast, data from the Gamar Malamo station reveal a significant wave height ranging from 0.02 to 4.28 meters and a significant wave period from 0.20 to 6.85 seconds. The study indicates that BMKG and satellite data produce consistent wave height calculationsKeywords: Wave Forecasting, Sea Waves, Weda Bay, Altimetry Satellite